Analisis Manfaat Aplikasi SakuJapan untuk Pembelajaran Keterampilan Dasar Bahasa Jepang Mahasiswa di Sekolah Vokasi IPB - Bagus Hardika; Mahesa Dzikri Kurniawan; Daffarizqy Prastowiyono; Muhammad Adzka; Humanisa Rubina Lestari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Language is crucial for human interaction, making foreign language education, especially Japanese, increasingly vital in the global era. Indonesia holds the second-highest number of Japanese learners globally. This study evaluates SakuJapan, a Japanese learning application, to enhance basic Japanese skills among IPB Vocational School students. Using a quantitative descriptive approach with 20 students, data was collected via online questionnaires on usage, features, effectiveness, and motivation. Findings show SakuJapan is an effective and user-friendly tool; 75% of respondents regularly use features like Hiragana, Katakana, vocabulary, and practice questions. The application scored an average effectiveness of 4.3 out of 5, with 85% of users gaining confidence in basic Japanese. While generally well-received, suggestions include offline features, varied exercises, adjustable game difficulty, and more audio, daily conversations, and JLPT-standardized tests. These insights guide further development for a more comprehensive and adaptive learning platform.